The Crisis of Communication Ethics in the Post-Truth Era: A Review of Islamic Moral Philosophy on the Phenomenon of Digital Simulacra - Ahmad Sofian; Rubino; Muhammad Randicha Hamandia; Zhila Jannati (Indonesian Journal Publisher, 2026)
Modern communication today exists in a highly controlled setting which combines algorithm-driven content delivery with artificial media and the rise of post-truth falsehoods. Digital simulacra enable people to confuse actual existence with virtual existence which results in false information and knowledge division and public trust erosion. This study examines how the post-truth era creates an ethical crisis for communication through Jean Baudrillard's simulacra theory while Islamic moral philosophy serves as an alternative ethical system. The study uses qualitative library research methods to examine current research articles and philosophical works and academic texts that focus on digital communication and post-truth cultural practices and communication ethics and Islamic knowledge systems. Digital simulacra and algorithm-based communication systems create hyperreality but they also disrupt established truth standards and traditional ethical systems. Islamic moral philosophy provides a complete normative system through its fundamental concepts of al-haqq (truth) and shiddiq (truthfulness) and amanah (trustworthiness) and tabayyun (verification) and prophetic communication ethics and Qur’anic principles of al-qaulan. These principles provide ethical guidance for strengthening information integrity, promoting responsible digital citizenship, and cultivating an akhlak based digital ecosystem. The study introduces Digital Prophetic Communication Ethics as a reconstructive framework which helps solve the ethical and epistemological issues arising from present-day digital communication.